Synthesis, characterization, DFT calculations and antimicrobial activity of pentagonal-bipyramidal Zn(II) and Cd(II) complexes with 2, 6-diacetylpyridine-bis(trimethylammoniumacetohydrazone). Issue 18 (16th September 2016) - Brađan, Gabrijela; Pevec, Andrej; Turel, Iztok; Shcherbakov, Igor N.; Milenković, Milica; Milenković, Marina; Radanović, Dušanka; Čobeljić, Božidar; Anđelković, Katarina
Abstract: Isothiocyanate complexes of Zn(II) and Cd(II) with the condensation product of 2, 6-diacetylpyridine and trimethylammoniumacetohydrazide (Girard's T reagent) were synthesized, characterized, and their antimicrobial activities were evaluated. The structures of the complexes were determined by elemental analysis, IR, and NMR spectroscopy. The crystal structure of the Zn(II) complex was also determined. Quantum-chemical calculations of the geometry and total energy of isomers of 2, 6-diacetylpyridine-bis(trimethylammoniumacetohydrazone) were performed in vacuum and methanol solution, with the aim to explain conformational behavior and E / Z isomerism of this compound. DFT calculations of the molecular structures and the relative stabilities of linkage isomers of the Cd(II) complex showed that the isomer with N–Cd–N coordination of SCN − is the most stable. Complexes of Zn(II) and Cd(II) exhibited low to moderate activity against the tested microbial strains. Abstract :